PERAN ASTRONOMI TRADISIONAL DAN BINTANG DALAM PENETUAN MUSIM TANAM SERTA PANEN PERSPEKTIF ILMU FALAK - Md, Putri Damayanti; Wakia, Nurul (HISABUNA: Jurnal Ilmu Falak, 2025)
ABSTRACT This study examines how traditional astronomical knowledge is utilized by local communities through the observation of stars and celestial phenomena to determine the appropriate timing for agricultural activities, particularly planting and harvesting seasons. From the perspective of Islamic astronomy (Ilmu Falak), the research focuses on identifying the roles of specific stars and analyzing the contributions of traditional astronomical practices in the Luwu region. This research employs a qualitative method with a library research approach and analyzes data using interdisciplinary, historical, and comparative methods. The findings reveal that traditional astronomy and the role of certain stars play a significant role in determining planting and harvesting seasons. The people of Luwu have, for generations, relied on the positions of specific stars such as Orion, Sirius, the Pleiades, and Crux as indicators of seasonal changes. This research can be implemented in various fields, particularly in agriculture, education, and cultural preservation in Luwu. In agriculture, traditional astronomical knowledge can be integrated with modern weather technology to determine optimal planting and harvesting times. The Ilmu Falak approach enriches the interpretation of related verses through the analysis of celestial bodies’ orbits and the position of the universe, demonstrating harmony between religious and scientific perspectives. Keywords: Traditional Astronomy, Islamic Astronomy (Ilm al-Falak), Planting Season, Harvest, Luwu, Stars, Islamic Science